2015
DOI: 10.1039/c5cc06653k
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed silylation of p-quinone methides: new entry to dibenzylic silanes

Abstract: An efficient and general copper(i)-catalyzed silylation of p-quinone-methides is described. Non-symmetric dibenzylic silanes are obtained in high yields under mild reaction conditions. These compounds can be used as bench-stable benzylic carbanion precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(27 citation statements)
references
References 63 publications
1
25
0
1
Order By: Relevance
“…A silylation-aromatization sequence involving coppercatalysed conjugate 1,6-addition to para-quinone methides was demonstrated by Tortosa and co-workers in 2015 (285a-i -286a-i, Scheme 88). 108 A variety of benzylsilanes, which could serve as bench-stable benzylic carbanion precursors, were obtained in good yields under this mild transformation.…”
Section: 2-addition To Het-het Double Bondsmentioning
confidence: 99%
“…A silylation-aromatization sequence involving coppercatalysed conjugate 1,6-addition to para-quinone methides was demonstrated by Tortosa and co-workers in 2015 (285a-i -286a-i, Scheme 88). 108 A variety of benzylsilanes, which could serve as bench-stable benzylic carbanion precursors, were obtained in good yields under this mild transformation.…”
Section: 2-addition To Het-het Double Bondsmentioning
confidence: 99%
“…This study again proofed that an enol system, as in the case of unsaturated ketones which is not easy to isolate, could be modified in such way that the resultant intermediate is highly stable. For example, Tortosa [65] showed that this type of catalytic system could be applied to the quinone methide system 162, which is equivalent to dienones (Scheme 29). In this case, however, instead of forming an enol, a highly stable phenol resulted from the addition of silicon at the methide position.…”
Section: Additions To Unsaturated Compoundsmentioning
confidence: 99%
“…Quinone methides (QMs) are electrophilic compounds composed of a cyclohexadiene core bearing a carbonyl either ortho or para to an exocyclic alkylidene unit [1,2]. Due to their electrophilicity [3][4][5][6], QMs have been used in a variety of biological and medicinal processes [1, 2,7], are present within natural products and pharmaceuticals [1,2,[8][9][10][11], and have been applied as electrophiles in a variety of synthetic reactions [1,2,[12][13][14][15][16][17][18]. While ortho-QMs have been used extensively in enantioselective catalysis [19], particularly as components in formal [4+2] cycloaddition reactions, the use of para-QMs has only recently received increased attention [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%